Efektivitas Model Inquiry Learning Berbantuan Komik Virtual terhadap Kemampuan Menulis Hikayat - Muhamad Sholehhudin; Salsabila Nurhaliza Putri Isnani; Cahyo Hasanudin (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2026)
The Inquiry Learning model is a student-centered approach that involves exploration, questioning, and direct discovery of concepts. This study aims to test the effectiveness of the Inquiry Learning model, supported by virtual comics, in improving students’ ability to write folktales. Virtual comics are used as an interactive visual medium to help students understand the elements of folktales, such as plot, characters, setting, and moral message. This study employed a quasi-experimental method with a one-group pretest–posttest design and involved 20 students in the 10th grade at SMK Abu Darrin, Bojonegoro. Data were collected through a folktale writing test and analyzed using N-Gain calculations and a Paired Sample t-test. The results indicate a significant improvement in writing ability, evidenced by an increase in the average score from 49.6 on the pretest to 67.5 on the posttest. The N-Gain value of 0.34 falls into the moderate category. The t-test yielded a calculated t-value of 9.73, which is greater than the critical t-value of 2.093, thus rejecting H₀. The Inquiry Learning model supported by virtual comics has not only proven effective in improving students’ narrative writing skills but also contributes to modernizing the teaching of classical literature through the integration of interactive digital media, as well as reconstructing the archaic values of narratives into a more creative and systematic written form. Keywords: nquiry Learning Model, Virtual Comics, Narrative